Comparative Retrospection of Civil Society Concepts - Gorchilova, Denitsa (Research Papers, 2010)
Many different civil society organizations and structures reemerged on the public scene in Bulgaria in the years after 1989. That brought to light the question of developing a conceptual frame for their study and analysis. The current text contains the first stage of its making – the retrospective look at civil society concepts from antiquity to the present days. The study examines their boundaries and the views of different scholars on the relations state – business – citizens – civil society.